2022
DOI: 10.1016/j.ymgmr.2021.100837
|View full text |Cite
|
Sign up to set email alerts
|

Risk mitigation behaviors to prevent infection in the mitochondrial disease community during the COVID-19 pandemic

Abstract: Background A challenge during the COVID19 pandemic has been widespread adherence to risk-reducing behaviors. Individuals with mitochondrial disease (MtD) are special population with an increased risk of morbidity associated with infection. Purpose To measure risk mitigation behaviors (RMBs) in families affected by MtD and identify factors that may influence these behaviors. Methods An online questionnaire was distributed in April and June 202… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
1
4
1
Order By: Relevance
“…Vaccine hesitancy in this community was more prevalent toward the COVID-19 vaccine than toward other routine childhood vaccinations. While other studies have reported an association between receipt of the annual flu vaccine and COVID-19 vaccine compliance, our population demonstrated a dichotomy of high flu shot compliance but also high COVID-19 vaccine hesitancy ( Phan et al, 2022 , Gordon-Lipkin et al, 2022 ). Only half of families felt that the benefits of the vaccine outweigh the risks and many families expressed concern that their child will deteriorate as a result of vaccination.…”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations
“…Vaccine hesitancy in this community was more prevalent toward the COVID-19 vaccine than toward other routine childhood vaccinations. While other studies have reported an association between receipt of the annual flu vaccine and COVID-19 vaccine compliance, our population demonstrated a dichotomy of high flu shot compliance but also high COVID-19 vaccine hesitancy ( Phan et al, 2022 , Gordon-Lipkin et al, 2022 ). Only half of families felt that the benefits of the vaccine outweigh the risks and many families expressed concern that their child will deteriorate as a result of vaccination.…”
Section: Discussioncontrasting
confidence: 78%
“…A questionnaire was designed by an expert panel at our institution including specialists in neurodevelopmental disabilities, genetics, infectious disease and sociology. Questions were based on prior surveys from this group as well as publicly available vaccine questionnaires from Pew Research and the National Foundation for Infectious Disease ( Gordon-Lipkin et al, 2022 ). We deployed the questionnaire via a cloud-based platform through MtD patient advocacy groups, including, the United Mitochondrial Disease Foundation (UMDF), People Against Leigh Syndrome, and the North American Mitochondrial Disease Consortium.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…36 Of note, the viral infections documented in the households for this study were similar to a multi-year cohort of paediatric healthy controls recently published. 37 Our VirScan and SARS-CoV-2 studies indicate that despite adherence to RMBs during the COVID-19 pandemic by families with a child with MtD, 38 viral infection is pervasive.…”
Section: Viral Infections In Households Via Phage Display and Immunop...mentioning
confidence: 99%
“…Recently, we showed that families affected by MtD display high levels of adherence to these risk mitigation behaviors (RMBs) during the pandemic, likely due to fear of potential sequelae associated with infection. 8 Despite these high levels of adherence amongst the MtD community, the home can still act as a hub for infection from household members 9 , many of which may be undiagnosed. 10 As such, we hypothesized high penetrance of COVID-19 into households in the pediatric MtD community.…”
Section: Introductionmentioning
confidence: 99%